Shaping the Quranic Generation from an Early Age (Study of Imtaq Programme Management in PAUD Akbar, Kaur Regency, Bengkulu) - Julianto, Alfin; Siregar, Nelda Sari (PPSDP International Journal of Education, 2024)
This study discusses the management of the imtaq program at PAUD Akbar. The problems discussed in this study are planning, implementation, and assessment of the imtaq program at PAUD Akbar. This study uses descriptive qualitative research. Data collection techniques include interviews, observation, and documentation studies. Data analysis techniques using data reduction, data presentation, and conclusion drawing. The results of the research are: First, Akbar PAUD has formulated imtaq program planning. The imtaq program is a flagship program because it is in accordance with the need to obtain religious education in line with the vision and mission of PAUD Akbar. Program planning consists of daily, weekly, and annual programs. Secondly, the implementers of the imtaq program include the principal, teachers, parents, and the community who work together in implementing the program. Teachers apply four learning methods, namely, the play method, the storytelling method, the singing method, and the demonstration method. Third, teacher assessment is carried out in the form of assessments on aspects of child development and cognitive, affective, and psychomotor aspects. The assessment is carried out by teachers by conducting observations, children’s self-assessment, and portfolio assessment. The results of the follow-up of the program are still continued, but there are some improvements in improving facilities and infrastructure, teacher competence, and variations in learning models.